2010
DOI: 10.1002/elan.201000113
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Monitoring the Acid and Acidic Urea‐Induced Unfolding of Hemoglobin and Its Electrocatalytic Ability

Abstract: Acid and acidic urea-induced unfolding of hemoglobin (Hb) was investigated using protein-film-based electrochemical method. The conformational transition of Hb was monitored through the change of direct electrochemical response of Hb. The heme groups in Hb detached from their native binding sites after pH < 4.0. Spectral experiments fully supported the results. Furthermore, the catalytic ability of Hb was enhanced 15 times under the optimal unfolded conditions of pH 2.0 PBS containing 3.0 mol L À1 urea. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
1
12
1
Order By: Relevance
“…The sudden decrease of Ipc was attributed to unfolding of the Hb, in particular changes in the heme pocket and its exposure to solvent. This was different from the research results of Zhao et al, 21 in which the current rate of sharp change was between pH 4.0 and 2.0. This was probably due to the fixed method of Hb to electrode.…”
Section: Acid-induced Unfolding Of Hb On Mpa-modified Electrodecontrasting
confidence: 99%
See 3 more Smart Citations
“…The sudden decrease of Ipc was attributed to unfolding of the Hb, in particular changes in the heme pocket and its exposure to solvent. This was different from the research results of Zhao et al, 21 in which the current rate of sharp change was between pH 4.0 and 2.0. This was probably due to the fixed method of Hb to electrode.…”
Section: Acid-induced Unfolding Of Hb On Mpa-modified Electrodecontrasting
confidence: 99%
“…Previous research 10,21 showed that the electrochemical response increased upon the unfolding of Hb induced by the denaturant urea because of the electrical active center exposure. Figure 1A shows typical cyclic voltammograms (CVs) of different chemically modified electrodes in the absence or presence of 8.0 M urea as the denaturant.…”
Section: Urea-induced Unfolding Of Hb On Mpa-modified Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…Protein unfolding / folding mechanisms are traditionally investigated by spectroscopic techniques (fluorescence, UV-Vis, circular dichroism) [1]. However, electrochemical methods have been developed to investigate protein unfolding mechanisms using, protein filmmodified electrodes [2][3][4][5][6] and mercury electrodes [7][8]. Detection of protein unfolding at proteinfilm electrodes is generally based on the release of redox-active groups, such as the haem groups of haemoglobin (Hb).…”
Section: Introductionmentioning
confidence: 99%